Changing epidemiology of poisoning in Central India: shifting poles from male farmers to young house wives - Gupta, Rupesh; Kumar Baghel, Praveen; Gupta, Hariom; Kumar Jain, Mahendra; Khadanga, Sagar; Kumar Tagore, Praveen; Saluja, Rohit; Kesharwani, Priyanka (International Journal of Medical Research and Review, 2016)
Introduction: Acute self infliction of poisoning is very common among young in developing countries. The epidemiology of poisoning changes time to time and varies region to region. In south India, organophosphorus compound poisoning has been more common as compared to Aluminium phosphide poisoning in north India. All over India males are more commonly reported to poison themselves. Poisoning in farmers has been reported more commonly than in any other profession. Madhya Pradesh is situated in central part of India, where agriculture is the predominant source of income. There is a knowledge gap in epidemiology of poisoning in this region. Methods: This is a hospital based observational type cross sectional study over nearly 2 years. Results: Out of the 550 number of study participants about 90% were younger than 40 years. Females were more common than males in all age groups. Poisoning was more common in married population in both the genders. House wives followed by unemployed students were the most vulnerable populations. Farmers constituted only about 10% of total cases. Organophosphorus compounds were the most common type of poisoning contributing to almost one fourth of the total cases followed by Zinc phosphide, Aluminium phosphide, oleander and ethylene dibromide poisoning in decreasing order. The overall mortality was 9.8% (n=54). The case fatality rates of various agro-chemicals in decreasing order were Aluminum phosphide (44.7%), ethylene dibromide (17.6%), and organophosphorus (7%). These 3 poisonings contributed to 92.5% of all deaths. Death was more common when the time lag to hospitalization was > 6 hours. Conclusion: Younger age group, female sex and housewives were the most vulnerable group. The case fatality rate of various poisonings in decreasing order were Aluminum phosphide (Celphos) poisoning followed by EDB and OPC.